ADVOCACY FOR THE HISTORY OF PEDAGOGY - Aura HAPENCIUC (Association of Social and Educational Innovation, 2021)
The paper Advocacy for the history of pedagogy focuses upon three objectives: a) the highlighting of the importance of the pedagogy history as a science of education with an autonomous character, based upon an important type of investigation at the level of fundamental pedagogical research; b) the presentation, in synthetic vision, of the evolution of pedagogy in Russia; c) the identification of the key directions of evolution of pedagogical thinking in Russia in the contemporary period. Among the pedagogies with contributions to the history of pedagogy, we chose the studies of two representative contemporary authors: E.D.Dneprov and B.M.Bim-Bad.The conclusions set the necessary premises to be able to support the main axiomatic foundations of modern pedagogy, in the context of the transition from the pre-modern historical epoch to the modern historical period.